Dinamika Pembelajaran Daring Bagi Mahasiswa Kelas Reguler Malam Akuntansi Pajak - Taufik Kurachman (LPPM-STPI, 2020)
The occurrence of the Covid-19 pandemic in Indonesia is not an obstacle for academics to continue to carry out their functions in educating and educating the nation's children from elementary to tertiary level, including what has been done by the Indonesian Taxation High School (STPI) academics to continue the lecture process through online learning. But is online learning effective enough to be implemented for regular night class students? To answer this problem, the researcher used level 2 (two) action research methods with data collection techniques through questionnaire link distribution, observation and finally data collection using poliangulation where if all data and information have been collected, analysis will be carried out using logico-inductive analysis. The study provides an important picture where in its implementation, the provision of course materials with online learning is not optimal, but on the other hand students still feel the benefits of online learning in the form of time efficiency, cost and energy and flexibility in implementing learning activities. Students hope that online learning can be returned to face-to-face through classical methods while still paying attention to covid-19 health procedures and protocols